2022
DOI: 10.3390/biomedicines10123277
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Bronchiolitis Obliterans Syndrome after Lung Transplant: Between Old Knowledge and Future Perspective

Abstract: Bronchiolitis obliterans syndrome (BOS) is the most common form of CLAD and is characterized by airflow limitation and an obstructive spirometric pattern without high-resolution computed tomography (HRCT) evidence of parenchymal opacities. Computed tomography and microCT analysis show abundant small airway obstruction, starting from the fifth generation of airway branching and affecting up to 40–70% of airways. The pathogenesis of BOS remains unclear. It is a multifactorial syndrome that leads to pathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 168 publications
0
4
0
Order By: Relevance
“…У детей ОБ в большинстве случаев появляется после перенесенной тяжелой инфекции нижних дыхательных путей -постинфекционный облитерирующий бронхиолит [2]. Для данного клинического синдрома характерна прогрессирующая одышка, тахипноэ, стойкая гипоксемия, продуктивный кашель при отсутствии паренхиматозного поражения легких [4,5].…”
Section: мцнп «новая наука»unclassified
“…У детей ОБ в большинстве случаев появляется после перенесенной тяжелой инфекции нижних дыхательных путей -постинфекционный облитерирующий бронхиолит [2]. Для данного клинического синдрома характерна прогрессирующая одышка, тахипноэ, стойкая гипоксемия, продуктивный кашель при отсутствии паренхиматозного поражения легких [4,5].…”
Section: мцнп «новая наука»unclassified
“…[ 34 ] Computed tomography and micro-CT analysis show many small airway obstructions below the fifth-generation airway branches, with 40% to 70% of the airway affected to varying degrees, an outcome not explained by acute rejection, infection, or other coexisting disease. [ 35 ] Combining quantitative parametric response mapping with qualitative CT image features can improve diagnostic level for BOS. [ 36 ] One study found damage to the pIgR/IgA system in patients with BOS, and it was hypothesized that patient morbidity was associated with an increased likelihood of local infection.…”
Section: Hotspots and Frontiersmentioning
confidence: 99%
“…1 Lung transplant is a therapeutic option in selected patients with end-stage lung disease. 2,3 The lungs are the only solid transplant organs exposed to the environment, including air pollution, bacteria and viruses. The large amount of lymphoid tissue in the lungs and heavy immunosuppression are associated with a high risk of contracting CMV infection, which occurs in 30%-80% of lung transplant patients.…”
Section: Introductionmentioning
confidence: 99%
“…Human cytomegalovirus (CMV) belongs to the family of herpes virus and is the most common infection after solid organ transplant 1 . Lung transplant is a therapeutic option in selected patients with end‐stage lung disease 2,3 . The lungs are the only solid transplant organs exposed to the environment, including air pollution, bacteria and viruses.…”
Section: Introductionmentioning
confidence: 99%